California bearing ratio correlation with soil index properties - Mak, Wai Kin (2006)
California Bearing Ratio (CBR) is a commonly used indirect method to assess the stiffness modulus and shear strength of subgrade in pavement design works, however; civil engineers always encounter difficulties in obtaining representative CBR value for design of pavement. Over the years, many correlations had been proposed by various researchers in which the soil index properties were used to develop these correlations. A study was carried out to find the correlation between CBR values with soil index properties that best suit the type of soils in Malaysia. Analyses were carried out based on the published correlations and soil data obtained from two highway project sites. Based on the results, it is observed that the current published correlations are not suitable to be used in Malaysia. In addition, no typical range could be found based on the soil index properties. A correlation had been proposed in the study to predict the CBR values at top face of the soil sample for fine-grained soil based on the soil data collated. These correlations were developed based on the maximum dry density and optimum moisture content.